“I Feel Powerless”: Frontline Insights Into Policy Gaps and Structural Injustices in the Care of People Experiencing Homelessness with Acquired Brain Injury - Jubinville, William; Bottari, Carolina; Ducharme, Roxanne; Thibault, Geneviève; Wagner, Vincent; Roy, Laurence (International Journal on Homelessness)

(untitled) (Western Libraries, University of Western Ontario, 2026)
Purpose: Acquired brain injury (ABI) is disproportionately prevalent among people experiencing homelessness, who often face multiple overlapping health and social needs. Yet, healthcare services remain fragmented and ill-equipped to respond to these complex needs. Consequently, existing healthcare systems often fail to provide continuous and coordinated responses adapted to this population’s realities. This study aimed to document gaps in healthcare services for people with ABI who are experiencing or at risk of homelessness and to identify the barriers to implementing services to prevent homelessness for this population. Material and methods: A qualitative descriptive study was conducted, involving three focus groups composed of health professionals and community workers from the homelessness and ABI sectors. Data were analyzed using Paillé and Mucchielli’s thematic analysis method. Results: Participants reported: 1) Complexity of access to health services, 2) Systemic lack of competence in the care of individuals with ABI in situations of social vulnerability, 3) Implicit norms of conformity within the health care system and rapid labeling, and 4) Individual and community consequences. Conclusion: This study highlighted several systematic gaps in healthcare services offered to this population. Findings are discussed in the context of stigmatisation theories, which are used to explore the impact of stigma on access to and quality of services.